ERGONOMIC EXERCISEDECREASES BLOOD PRESSURE, PULSE AND STRESS LEVEL IN PRIMARY HYPERTENSION PATIENTS AT SOKOBANAH SUB-DISTRICT, SAMPANG DISTRICTMADURA - holilah holilah (Aloha International Journal of Health Advancement (AIJHA), 2019)
Hypertension is a condition in which the blood pressure elevated above 140/90 mmHg. Stress is one of the factors that cause hypertension. In this case, one of the alternatives to improve the hypertensive patients’ physical condition of blood flow and nerves is ergonomic exercise. This study purposed to analyze differences in blood pressure, pulse, and stress level through the ergonomic exercise in patients with primary hypertension at the Sokobanah sub-district, Madura Regency. This research used a quantitative research method with a pre-experimental one-group pretest-posttest. The population was 55 patients. Inconsequent, 48 people were taken as a sample by simple random sampling. Data analysis with Wilcoxon signed-rank test was conducted for the analysis and it showed differences on blood pressure (p-value: 0,000), pulse (p-value: 0,000) and stress level (p-value: 0,000) in primary hypertensive patients before and after being given ergonomic exercises at SokobanahSubdistrict, Sampang Madura Regency.